Enhancing Justice Through Responsive Law in Indonesia - Rochmadi Rochmadi; Zainal Arifin Hoesein (Asosiasi Penelitian dan Pengajar Ilmu Hukum Indonesia, 2024)
Responsive law in Indonesia is an approach that aims to adapt the legal system to the dynamics and needs of a growing society. This article analyzes how the application of responsive law can improve justice and the effectiveness of law enforcement in Indonesia. The methodology used in this study includes a qualitative analysis of existing legal policies, in-depth interviews with legal practitioners, and case studies from several regions in Indonesia that apply the principles of responsive law. The results of the study indicate that the application of responsive law is not only able to answer emerging social challenges, but also strengthen the legitimacy of law in the eyes of the community. By integrating the values of justice and local needs in the law-making process, it is hoped that the Indonesian legal system will become more inclusive and responsive to community aspirations. This study recommends the development of more flexible and adaptive legal policies to ensure more equitable justice throughout Indonesia.